Gravitational Aeration Tower Filter System to Increase the Dissolved Oxygen Amount for Iron Removal in Groundwater - Mat Radzi, Mohammad Erwan Zaki; Wahab, M. S.; Sahdan, M. Z.; Hamdan, R.; Zakariah, R. A. (International Journal of Integrated Engineering, 2020)
This paper discusses the Gravitational Aeration Tower Filter System (GATS) aims to increase the amount of Dissolved Oxygen (DO) for iron removal in groundwater. The groundwater is mostly used in remote areas. The presence of a large volume of iron contained in the groundwater will subject to water contamination besides limiting the lifespan of existing water to filter the contaminants. Pre-treatment systems i.e., aeration technique is often used to lower the amount of iron ​​contained in the groundwater. One of the proposed aeration techniques i.e., the GATS has been designed in this work. The GATS is tested to observe its effectiveness to increase the DO and iron removal in the water. The area of study is conducted in Kampung Majid Ibrahim, Simpang Renggam. The initial value of the iron in the tubewell is between 1.4 mg/l to 2.3 mg/l, which has exceeded the limit standard of 0.3 mg/l. Data collection is carried out in-situ testing using AQUAREAD AP2000 and Hanna High Iron Checker. The flow rate through the GATS is fixed to 5.5 L/min, with air parameters are varied. The results of the GATS test demonstrate the DO percentage increases up to 90.50 % and the percentage of iron removal is up to 10.24% with the airflow of 1.0 L/min.